2021
DOI: 10.1042/bsr20204421
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine Bu-Shen-Jian-Pi-Fang attenuates glycolysis and immune escape in clear cell renal cell carcinoma: results based on network pharmacology

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common malignant type of kidney cancer. This study aims to explore the underlying mechanism and potential targets of the traditional Chinese medicine Bu-Shen-Jian-Pi-Fang (BSJPF) in the treatment of ccRCC based on network pharmacology. After obtaining the complete composition information for BSJPF from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform, we analyzed its chemical composition and molecular targets and then estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Curcumin inhibited cell proliferation and motility by suppression of TROP2 in bladder cancer [ 18 ]. In addition, the traditional Chinese medicine Bu-Shen-Jian-Pi-Fang has been reported to attenuate the glycolysis and immune escape of clear cell RCC [ 19 ]. Nevertheless, effective drugs are still needed to improve the prognosis of RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin inhibited cell proliferation and motility by suppression of TROP2 in bladder cancer [ 18 ]. In addition, the traditional Chinese medicine Bu-Shen-Jian-Pi-Fang has been reported to attenuate the glycolysis and immune escape of clear cell RCC [ 19 ]. Nevertheless, effective drugs are still needed to improve the prognosis of RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced renal cancer is mainly treated by surgical resection of tumor lesions combined with biological therapy, endocrine therapy, and immunotherapy, which is not effective and patients are prone to intolerance [ 3 ]. Based on the holistic view and syndrome differentiation, traditional Chinese medicine believes that renal cell cancer is caused by deficiency of kidney qi and aggregation of pathogenic toxins [ 4 ]. The application of TCM treatment can improve the healthy qi, stabilize the cancer focus, prevent recurrence and metastasis, and thus achieve the purpose of improving the quality of life of patients and prolonging their survival [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of cardiotoxic protective drugs with unique pharmacological effects from TCM has become a new direction ( 36 ). For example, Zheng et al found that the TCM Bu-Shen-Jian-Pi-Fang could inhibit tumor proliferation by enhancing GLUT-1 related glycolysis and may alter the immune-rejection microenvironment in renal cell carcinoma patients ( 37 ). Ginsenoside Re functions as an antioxidant, protecting cardiomyocytes from oxidant injury induced by exogenous and endogenous oxidants, and protects against apoptotic cell death ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%